Crystal structure of 4-(2-bromo-4-(6-morpholino-3-phenyl-3H-benzo[f]chromen-3-yl) cyclohexa-2,5-dien-1-yl)morpholine, C33H31BrN2O - Liu Fu-Jie; Wang Guo-Xi (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C31H31BrN2O3, monoclinic, P21/c (no. 14), a = 10.2014(15) Å, b = 21.499(3) Å, c = 12.1885(18) Å, β = 95.175(2)°, V = 2662.3(7) Å3, Z = 4, Rgt (F) = 0.0521, wRref (F2) = 0.1993, T = 296(2) K.